Analisis Komunikasi Verbal dan Non Verbal Perselingkungan Suami Istri pada Film “Ipar Adalah Maut” - Hadi Hidayat,; Putra Perdana , Adhitya (Jurnal Ilmu Komunikasi, 2025)
Film “Ipar Adalah Maut” is a film directed by Hanung Bramantyo which was adapted from Elizasifaa's Tik Tok content with millions of viewers. Eliza apparently created this content based on the true story of a person who did not want his identity revealed. This research analyzes verbal and non-verbal communication that depicts infidelity in the film "In-Law Is Death". Using a descriptive qualitative approach, this research aims to reveal how verbal (dialogue, narration) and non-verbal elements (facial expressions, body language, setting) in the film represent the dynamics of infidelity and its impact on the husband and wife relationship. Data was collected through observation and analysis of film content. The research results showed that there was verbal communication that led to infidelity, one of which was dialogue between the husband and his wife via a telephone that had not been turned off so that the wife knew that there was an affair between her sister-in-law and her husband. In any non-verbal way, there is a suspicious expression on the husband's face when his son picks up the phone from a woman, but the written contact is written with the man's name, namely Mr. Junaidi, his fellow lecturer. There are several other verbal and non-verbal communications that lead to husbands cheating on their wives and even to having intimate relations. This film presents a deep message to the audience, especially that the affair was carried out between brothers, namely his own sister-in-law.